2011
DOI: 10.1111/j.1399-3089.2011.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Xenoreactive CD4+ memory T cells resist inhibition by anti‐CD44 mAb and reject islet grafts via a Th2‐dependent pathway

Abstract: Multiple applications of the anti-CD44 mAb could significantly inhibit donor-reactive CD4(+) memory T cells from rejecting grafts via a Th1-dependent pathway, but xenoreactive CD4(+) memory T cells can avoid the effects of anti-CD44 mAb to reject islet xenografts via a Th2-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recipient mice were treated with 180 mg/kg streptozotocin (STZ) intra-peritoneally (IP) to induce the diabetes model 18 . After three days, mice with a blood glucose level higher than 16.7 mM in two consecutive days were used for transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Recipient mice were treated with 180 mg/kg streptozotocin (STZ) intra-peritoneally (IP) to induce the diabetes model 18 . After three days, mice with a blood glucose level higher than 16.7 mM in two consecutive days were used for transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…injection of 180 mg/kg streptozotocin (Sigma-Aldrich). 19 Three days later, mice with blood glucose levels greater than 16.7 mM on 2 consecutive days were used for transplantation. Four hundred islets were transplanted under the kidney capsule of the recipient mice.…”
Section: Induction Of Diabetes and Islet Transplantationmentioning
confidence: 99%
“…A recent study in a non-autoimmune model demonstrated that administration of anti-CD44 prolonged survival of allogeneic islets after transplantation (Peng et al, 2011). This improvement was associated with greatly reduced accumulation of CD4+ T cells within the grafts and diminished levels of IFN-γ in the sera of treated mice.…”
Section: Targeting Cd44 On T Cells To Ameliorate Disease: the Examplementioning
confidence: 99%